Critérios normativos sobre influência da relação Aw/Af e esbeltez de alma no cálculo da resitência à flexão de vigas esbeltas em elementos de estruturas de aço. - FERNANDES, Rodrigo (2007)
This work contains a theoretical analysis of the behavior of plate girders. A plate girder has been calculated based on the criteria of the American standard Manual of Steel Construction Load and Resistance Factor Design (AISC, 1994), and checked by the Brazilian standard NBR 8800: Projeto e execução de estruturas de aço de edifícios (método dos estados limites) (ABNT, 1986), the revision project of the Brazilian standard Projeto de Revisão da NBR 8800: Projeto e execução de estruturas de aço e de estruturas mistas aço-concreto de edifícios (ABNT, 2003), the revision project of the Brazilian standard Projeto de Revisão da NBR 8800: Projeto de estruturas de aço e de estruturas mistas de aço e concreto de edifícios (ABNT, 2007) and the European standard Eurocode 3: Design of steel structures Part 1.1: General rules and rules for buildings (CEN, 1992). PFEIL (1989) has calculated a plate girder by using the Brazilian standard NBR 8800/86. The calculated dimension have been checked by the mentioned standards. NARAYANAN (1992 apud OWENS, KNOWLES E DOWLING, 1992) has dimensioned a plate girder by using the British standard BS 5950: Structural use of steelwork in building. Part 1: Code of practice for design in simple and continuous construction: hot rolled sections (BSI, 1990), which has also been checked by the mentioned standards. Furthermore, theoretical analyses related to the calculus of plate girders presented by many authors have been considered. The main goal is to assess the criteria utilized by the standards for the calculus of plate girders. From the obtained results, for the checked girders, by the standards and related theories, a comparative analysis among the utilized criteria by the standards has been made. The reached conclusion is that the Brazilian standard and its revision projects has identical criteria compared to the American standard for the calculus of plate girders. The European standard presents slightly different criteria compared to the American standard; however, both provide close results one compared to another. The theories utilized have also provided close results from those obtained by the standards.